Ensemble prediction of coastal flood risk arising from overtopping by linking meteorological, ocean, coastal and surf zone models - Ian Cluckie (Quarterly Journal of the Royal Meteorological Society, 2013)
This paper presents an integrated ‘Clouds-to-Coast’ ensemble modelling framework of coastal flood risk due to wave overtopping. The modelling framework consists of four key components: meteorological forecasts, wave–tide–surge predictions, nearshore wave models and surf zone models. This type of ensemble prediction approach allows us to estimate the probabilities of various outcomes and so improve our understanding of the reliability of results. It also provides a measure of the uncertainty associated with predictions, which can be particularly large for extreme storms, and allows us to assess how the uncertainty propagates from meteorological forecasts to overtopping and subsequent coastal flood risk predictions. Copyright © 2013 Royal Meteorological Society